First 236U data from the Arctic Ocean and use of 236U/238U and 129I/236U as a new dual tracer - Casacuberta, Núria; id_orcid:0 000-0001-7316-1655; Masqué, P.; Henderson, G.; Rutgers van-der-Loeff, M.; Bauch, D.; Vockenhuber, Christof; Daraoui, A.; Walther, C.; Synal, Hans-Arno; Christl, Marcus (Earth and Planetary Science Letters, 2016)
ISSN:0012-821X ISSN:1385-013X